2013
DOI: 10.1074/mcp.m112.019745
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic and Proteomic Analysis of Cytoskeletal Changes in Dexamethasone-Treated Trabecular Meshwork Cells

Abstract: Steroid-induced glaucoma is an iatrogenic condition resulting from the use of glucocorticoids. Glucocorticoids such as dexamethasone (DEX) 1 raise intraocular pressure (IOP) in ϳ40% of patients in the general population, and ϳ6% of these patients will go on to develop glaucoma (1, 2). This condition is similar to primary open angle glaucoma (1-3), and is caused by a restriction in fluid outflow through the trabecular meshwork (TM), resulting in an imbalance between the amount of aqueous humor produced and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 40 publications
3
67
0
Order By: Relevance
“…We then investigated whether the level of activated avb3 integrin was also increased in DEX-treated cells, since our previous studies have shown that DEX treatment not only upregulates the expression of avb3 integrin, but it causes an increase in its activation state. 19,20,32,33 Not surprisingly, both total and activated levels of avb3 integrin were increased in DEX-treated HTM cells compared with untreated (Figs. 7A, 7B) and EtOHtreated cells (Figs.…”
Section: Dex-induced Reduction In Phagocytosis Corresponds With An Inmentioning
confidence: 87%
See 1 more Smart Citation
“…We then investigated whether the level of activated avb3 integrin was also increased in DEX-treated cells, since our previous studies have shown that DEX treatment not only upregulates the expression of avb3 integrin, but it causes an increase in its activation state. 19,20,32,33 Not surprisingly, both total and activated levels of avb3 integrin were increased in DEX-treated HTM cells compared with untreated (Figs. 7A, 7B) and EtOHtreated cells (Figs.…”
Section: Dex-induced Reduction In Phagocytosis Corresponds With An Inmentioning
confidence: 87%
“…51,52 Interestingly, a number of the molecules that could control the activity of avb5 and avb3 integrin signaling events have been reported to be upregulated in DEX treated TM cells. 32 Among them are filamin-B, caveolin-1, talin-1, paxillin, Src, and EPS8. Upregulation of caveolin-1 is particularly interesting since it has been reported to be a risk factor in glaucoma, [53][54][55] suggesting that alterations in caveolin-1/integrin signaling pathways could be involved in some glaucomas.…”
Section: Discussionmentioning
confidence: 99%
“…S6). Previous studies in other cell types have shown that activation of glucocorticoid receptors and adrenergic receptors (i.e., catecholamine receptors) leads to downstream rearrangements of cytoskeletal actin via multiple pathways including SGK1, ERK, RhoA/ROCK1, and cAMPdependent protein kinase A signaling (26)(27)(28)(29)(30)(31), providing candidate pathways that could provide further insight into our observed phenomenon. Of note, erythrocyte exposure to dexamethasone or epinephrine revealed no measurable changes in red cell concentration (i.e., no aggregation), size, shape, deformability, or margination (Figs.…”
Section: Glucocorticoids and Catecholamines Reduce The Mechanical Stimentioning
confidence: 99%
“…2,27 Studies implicate changes in cell and ECM stiffness as probable factors in the glaucoma process. 8,28,29 Recent elastic modulus determination in normal and glaucoma conditions [30][31][32] has indicated a relationship between increased TM tissue stiffness and open angle glaucoma, a change also identified in clinical studies. 7,33,34 Recognition of the Importance of Trabecular Tissue Motion Morton Grant can be credited with initiating the first studies to characterize TM motion.…”
Section: Cyclic Iop Changes Affect Signaling Pathways Of the Outflow mentioning
confidence: 99%